Pengembangan Kurikulum Bahasa Inggris di Binar Ilmu Boarding School - Uyun, Aip Syepul (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2023)
This article provides a brief description on how to develop the English curriculum in school. This measure has an essential position in our educational system. Language curriculum development is a comprehensive process for determining the needs of a group of learners in learning a language. That is why it is important to always check the appropriateness of the curriculum given by our government to be fit for our students. It can be manifested in the form of subject structures, teaching methods, and materials, This community service was carried out directly by evaluating the existing language curriculum from the government and also the local curriculum in school. The activities were conducted in one week at the beginning of the school year of 2023. The curriculum was discussed with the teachers and revised and adapted to the needs of the institution at Binar Ilmu Boarding School, Cimenyan, Bandung. The Participants were all teaching staff and all stakeholders school. These activities were carried out in three major stages. It was evaluating the existing curriculum, revitalizing the existing curriculum, and finishing. From those activities, it was produced the new curriculum of the institution namely BIBS Curriculum.